Development of Learning Activity Using Group Investigation for Promote Collaborative Problem Solving Competency of Mathayomsuksa 4 Students - Prasongsuk, Chanapon; Phuseerit, Thanadol (Journal for Developing the Social and Community, 2025)
Background and Aims: In the 21st century, scientific and technological advancements have rapidly transformed human lifestyles, presenting both opportunities and challenges. To adapt and maintain a quality life, it is essential for humans to develop key skills such as analytical thinking, problem-solving, and collaboration. This research aims to: 1) determine the effectiveness of Group Investigation learning activities in promoting collaborative problem-solving competency among Grade 10 students according to the 75/75 criterion; 2) compare the collaborative problem-solving competency of Grade 10 students after learning through Group Investigation techniques against the 75 percent criterion; 3) compare the academic achievement in Biology of Grade 10 students after learning through Group Investigation techniques against the 75 percent criterion; and 4) examine the satisfaction of Grade 10 students toward learning activities using Group Investigation techniques. Methodology: The sample group consisted of 39 students from Grade 10/11 in the second semester of the 2024 academic year at Sarakham Phittayakhom School. The sample was obtained through cluster random sampling, using classrooms as the sampling unit. The research instruments were: 1) Ten Group Investigation learning activity plans, totaling 15 hours; 2) A collaborative problem-solving competency assessment tool in the form of situational multiple-choice questions with 3 options, comprising 12 items covering all 12 sub-competencies; 3) An academic achievement test consisting of 30 multiple-choice questions with 4 options; and 4) A student satisfaction assessment questionnaire using a 5-point rating scale, comprising 20 items. Results: 1) The effectiveness of Group Investigation learning activities in promoting collaborative problem-solving competency among Grade 10 students on the topic of "Genetic Inheritance" in Biology was 90.34/81.79, which met the 75/75 criterion. 2) The collaborative problem-solving competency of Grade 10 students after learning through Group Investigation techniques on the topic of "Genetic Inheritance" in Biology had a mean score of 20.82 points, representing 86.75 percent of the total score, which was significantly higher than the 75 percent criterion at the .05 level of significance. 3) The academic achievement of Grade 10 students after learning through Group Investigation techniques on the topic of "Genetic Inheritance" in Biology had a mean score of 23.05 out of the total score, representing 76.83 percent of the total score, which was significantly higher than the 75 percent criterion at the .05 level of significance. 4) The satisfaction of Grade 10 students after participating in Group Investigation learning activities on the topic of "Genetic Inheritance" in Biology had an overall mean score of 4.23, indicating the highest level of satisfaction. Conclusion: The results of determining the effectiveness of Group Investigation learning activities to promote collaborative problem-solving competency among Grade 10 students on the topic of Genetic Inheritance in Biology revealed an effectiveness score of 90.34/81.79. When the learning activity model was implemented to promote collaborative problem-solving competency and academic achievement, the post-learning mean score was significantly higher than the 75 percent criterion at the .05 level of statistical significance. Furthermore, the students’ satisfaction after participating in Group Investigation learning activities was at the highest level.